2014
DOI: 10.1111/ajt.12640
|View full text |Cite
|
Sign up to set email alerts
|

Adapted Treatment of Epstein–Barr Virus Infection to Prevent Posttransplant Lymphoproliferative Disorder After Heart Transplantation

Abstract: Up to 35% of posttransplant lymphoproliferative disorder (PTLD) cases occur within 1 year of transplantation, and over 50% are associated with Epstein-Barr virus (EBV). EBV primary infection and reactivation are PTLD predictive factors, but there is no consensus for their treatment. We conducted a prospective single-center study on 299 consecutive heart-transplant patients treated with the same immunosuppressive regimen and monitored by repetitive EBV viral-load measurements and endomyocardial biopsies to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 42 publications
0
56
0
1
Order By: Relevance
“…In comparison with the historical data, this study showed an effective prevention of EBV-associated PTLD by closely monitoring the EBV load and taking preemptive measures. 2 The limitation of this approach is the induction of B-lymphocyte depletion for ~6 months, leading to infection susceptibility. It does not restore the cellular immunity against EBV and thus does not provide long-term control of …”
Section: Preemptive Rituximabmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with the historical data, this study showed an effective prevention of EBV-associated PTLD by closely monitoring the EBV load and taking preemptive measures. 2 The limitation of this approach is the induction of B-lymphocyte depletion for ~6 months, leading to infection susceptibility. It does not restore the cellular immunity against EBV and thus does not provide long-term control of …”
Section: Preemptive Rituximabmentioning
confidence: 99%
“…It is usually associated with poor prognosis, with a 5-year overall survival rate of 20%. 1,2 Its occurrence depends on the type of transplant received, the type of immunosuppression, its intensity and duration, and the age of the recipient. …”
Section: Introductionmentioning
confidence: 99%
“…Se ha evaluado prospectivamente la implementación de un protocolo de monitorización frecuente del VEB con reducción de la inmunosupresión guiada por la carga viral en pacientes pediátricos con trasplante de hígado (32) y se ha observado una diferencia estadís-ticamente significativa en la incidencia de ELPT, 16 % frente a 2 % (p < 0,05) con respecto a controles históri-cos. Además, se ha evaluado en adultos con trasplante cardíaco la combinación de monitorización de la carga viral de VEB, reducción de la inmunosupresión y uso anticipado de rituximab, lo cual también ha mostrado que reduce la incidencia de ELPT al comparar con controles históricos (33,34). Sin embargo, no hay ninguna recomendación actual sobre la periodicidad del seguimiento de la carga viral ni sobre las medidas terapéuticas para prevenir la aparición de ELPT; se requieren estudios prospectivos de alta calidad que evalúen la población en riesgo de ELPT y establezcan el papel de la monitorización y el tratamiento guiado por la carga viral de VEB.…”
Section: Prevenciónunclassified
“…1). 25 With this algorithm, all cases of EBV reactivation or primary infection were controlled, and no patients developed PTLD. Table 3 shows varying published preventive or curative attitudes, depending on EBV VL.…”
mentioning
confidence: 99%
“…Table 3 shows varying published preventive or curative attitudes, depending on EBV VL. 23,[25][26][27][28][29][30][31][32][33][34][35][36][37] Immunosuppression reduction. ISR is the widely acknowledged first-line approach, when possible.…”
mentioning
confidence: 99%